2022
DOI: 10.1111/jam.15697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of distinct modes of oxidative secondary injury generated in heat-treated cells of Escherichia coli with solid/liquid and complex/semi-synthetic media sets

Abstract: Aims:To characterize and evaluate oxidative secondary injury generated in heattreated Escherichia coli cells during recovery cultivation either on agar or in a broth of a semi-synthetic enriched M9 (EM9) medium and a complex Luria broth (LB) medium with different types of antioxidants.Methods and Results: E. coli cells grown in the EM9 and LB broth were heated at 50°C in a buffer (pH 7.0). Heated cells were recovered on the same kind of agar medium as that used for growth, with or without different antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The µ values of the untreated population were almost the same in inoculum sizes between the undiluted and the samples diluted one to five times every 10 fold which means even a 5-log cycle reduction in CFU, but, when CFU decreased by about 1.5 log cycles, that of the above heatinjured population decreased by 4%. UV irradiation of E. coli also showed slight decreases (10 and 16% with 1.4-and 4.0 log cycle decreases, respectively) , and γ irradiation also showed a 21% decrease under conditions with a 3.6-log cycle decrease in CFU (Vo 2021) . A similar decreasing trend was observed in the colony growth rate of heat-injured Cladosporium sphaerospermum spores on agar plates, with a 13% decrease in the colony formation rate for the sample resulting in a 0.7-log cycle decrease in CFU (Asada et al 2023b) .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The µ values of the untreated population were almost the same in inoculum sizes between the undiluted and the samples diluted one to five times every 10 fold which means even a 5-log cycle reduction in CFU, but, when CFU decreased by about 1.5 log cycles, that of the above heatinjured population decreased by 4%. UV irradiation of E. coli also showed slight decreases (10 and 16% with 1.4-and 4.0 log cycle decreases, respectively) , and γ irradiation also showed a 21% decrease under conditions with a 3.6-log cycle decrease in CFU (Vo 2021) . A similar decreasing trend was observed in the colony growth rate of heat-injured Cladosporium sphaerospermum spores on agar plates, with a 13% decrease in the colony formation rate for the sample resulting in a 0.7-log cycle decrease in CFU (Asada et al 2023b) .…”
mentioning
confidence: 93%
“…Stephens et al (2000) found that the survival of Salmonella after heat treatment was significantly increased when Oxyrase ® was added to the recovery medium, suggesting the involvement of an anaerobic effect due to oxygen removal and ROS (hydrogen peroxide) degradation by catalase activity contained in this enzyme preparation. Vo et al (2022) also examined the effect of antioxidants on the survival of heatinjured cells of E. coli using semi-synthetic (EM9) and complex (LB) media through development before heating and recovery after heating to rescue the injured bacteria. They reported that sodium thiosulfate and sodium pyruvate were highly effective in EM9 and LB, respectively, pointing out that anaerobic and ROS removal were the main factors in the mode of cell oxygen toxicity depending on the medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In inoculation, the spore population is distributed dispersedly on the paper disc, and subsequent growth is presumed to be immature or incomplete as a colony. Therefore, it is impossible to draw the growth within the the solid medium plate method and the GDA method (Takano and Tsuchido 1982) using liquid medium (Tsuchido 2017;2020a;Asada et al 2022;Vo et al 2022) . Of these two viability measures, the GDA method generally tracks the growth of microorganisms in a liquid medium using turbidity (OD) and measures how long the growth of the stressed population is delayed relative to that of the unstressed.…”
Section: Introductionmentioning
confidence: 99%
“…The colony counting (plate count) method is widely used to determine the viability of a variety of microorganisms. However, when microorganisms present in food or other environments are killed, the cell population will contain lethally injured cells that die immediately or during subsequent storage, as well as sublethally injured bacteria that have the ability to eventually revive, depending on conditions, to a greater or lesser extent (Andrew and Russell 1984;Tsuchido 2017;Vo et al 2022) . This injury can be detected as a delay in growth because of the time required for its repair in culture after lethal stress treatment.…”
Section: Introductionmentioning
confidence: 99%